Effects of Low Reynolds Number on Wake-Generated Unsteady Flow of an Axial-Flow Turbine Rotor - Takayuki Matsunuma; Yasukata Tsutsui (International Journal of Rotating Machinery)
The unsteady flow field downstream of axial-flow turbine rotors at low Reynolds numbers was investigated experimentally using hot-wire probes. Reynolds number, based on rotor exit velocity and rotor chord length Reout,RT, was varied from 3.2×104 to 12.8×104 at intervals of 1.0×104 by changing the flow velocity of the wind tunnel. The time-averaged and time-dependent distributions of velocity and turbulence intensity were analyzed to determine the effect of Reynolds number. The reduction of Reynolds number had a marked influence on the turbine flow field. The regions of high turbulence intensity due to the wake and the secondary vortices were increased dramatically with the decreasing Reynolds number. The periodic fluctuation of the flow due to rotor-stator interaction also increased with the decreasing Reynolds number. The energy-dissipation thickness of the rotor midspan wake at the low Reynolds number Reout,RT=3.2×104 was 1.5